Standardization and Adaptation Strategies in Marketing Communication: A Comparative Study Between Brazil and Argentina (Revista Interdisciplinar de Marketing, 2025)
This article investigates the digital marketing communication strategies adopted by Brazilian multinationals in the Latin American market, specifically focusing on identifying adaptation or standardization strategies across channels in different countries. The central research question is: do Brazilian multinationals standardize or adapt their social media communication when operating in foreign markets? To answer this question, we conducted a content analysis, examining the design and content of the Instagram accounts of Brazilian multinationals operating in Brazil and Argentina. At the end of the research, it was possible to observe a scenario in which the adaptation strategy is used by 100% of the companies analysed, which led to the creation of subcategories of analysis: Slightly adapted, Moderately adapted, and Highly adapted companies.